The development of Online Credit Exemption System (OCES) / Mohd Hanapi Abdul Latif, Rozmawati Mohd Yusof and Norulhidayah Isa - Abdul Latif, Mohd Hanapi; Mohd Yusof, Rozmawati; Isa, Norulhidayah (2011)
Online Credit Exemption System (OCES) is developed to automate the process of application and approval of credit exemption in UiTM Dungun, Terengganu. Applications for credit exemption are only open to new bachelor degree students who hold a diploma. They may come from various educational backgrounds. Some of them hold diplomas from UiTM, some from other institutions of higher learning and many are from different area of diploma programmes. At the moment, the process of credit exemption application is done manually. The student has to fill out and submit an application form to Academic Unit who has to manually check whether the course to be exempted is similar or equivalent to the course offered. The process of checking the courses applicable for credit exemption is timeconsuming since it is done in a non-automated system. More time is needed to locate and identify the similarity of the courses applied for exemption and the courses offered, especially if the students come from different institutions of higher learning and programmes. Hence, OCES has been developed using a Systems Development Life Cycle that is based on a waterfall model. There are six phases involved in the development of OCES, namely, project planning, analysis, design, development, implementation, testing and finally documentation. OCES allows for a more effective and efficient process of credit exemption application, which shorten the process and help Programme Coordinators or Academic Unit to approve applications automatically. Another benefit of this new system is that it is applicable to all academic programmes and can be implemented throughout UiTM. Formative evaluation was also conducted on the system to investigate user acceptance of OCES focusing on system usefulness and system ease of use. Result from the evaluation is used for making crucial changes on OCES based on users’ feedback.